Financial performance determinants: green intellectual capital, CSR expenditure, investment decisions, and corporate governance - Rinanta Nyata Esa Setiyanto; Amalia Ilmiani; Rika Adriyana (Business, Accounting, and Knowledge Journal, 2026)
This study investigates the effect of the Green Intellectual Capital Index, corporate social responsibility (CSR) costs, capital structure, investment decisions, and corporate governance on the financial performance of companies included in the SRI-KEHATI index. The SRI-KEHATI index represents firms that demonstrate sustainable business practices through strong corporate governance, environmental responsibility, and social engagement. The research focuses on companies listed on the Indonesia Stock Exchange during the 2019–2023 period. Secondary data were obtained from audited financial statements and annual reports. A purposive sampling technique was applied, resulting in a final sample of 20 companies with 100 firm-year observations. Data were analyzed using multiple linear regression with the support of SPSS software. The results show that CSR costs, capital structure, and corporate governance have a significant simultaneous effect on financial performance. However, the Green Intellectual Capital Index and investment decisions do not exhibit a significant influence. These findings provide empirical evidence on the role of sustainability-oriented expenditures and governance mechanisms in enhancing corporate financial performance, particularly among firms committed to sustainable and responsible business practices.